COMPARATIVE ANALYSIS OF TWOFISH AND BLOWFISH ALGORITHMS IN SECURING CSV (COMMA SEPARATED VALUES) DATA - Rizki Ali Akbar Pasaribu; Abdul Halim Hasugian; Aidil Halim Lubis (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Data security is a crucial aspect in the digital era, especially for the CSV (Comma Separated Values) data format, which is frequently used for data storage and exchange. This study aims to analyze and compare the performance of the Twofish and Blowfish cryptographic algorithms in securing CSV data. The analysis is based on three main parameters: encryption time, decryption time, algorithm security level, and changes to the encrypted or decrypted files. The Twofish algorithm is known for its Feistel structure and its flexibility with key sizes up to 256 bits, while Blowfish uses a variable key size up to 448 bits with a simple Feistel structure. The results show that Blowfish has higher encryption and decryption speeds than Twofish, with an average speed of around 275.85 ms for Blowfish and 655.672 ms for Twofish. However, Twofish excels in security. This study is expected to serve as a reference in selecting the right algorithm for securing CSV data based on specific user needs, both in terms of speed and security.